Experience of the game theory application in construction management - Peldschus, Friedel (Technological and Economic Development of Economy, 2008)
The game theory allows mathematical solutions of conflict situations. Besides the fairly established application to economical problems, approaches to problems in construction operation have been worked out. An overview of applications is given. Solution strategies for such engineering problems are collected. Furthermore, concrete application examples are presented and an overview of further potential applications is given. Solutions of two‐person zero‐sum games are discussed as well as approaches to fuzzy games. Lošimų teorijos taikymo patirtis statybos vadyboje Santrauka. Lošimų teorija teikia matematinių sprendimų konfliktinėse situacijose. Straipsnyje pateikta daug ekonominių problemų sprendimo pavyzdžių, sukurtų statybos valdymo problemų sprendimo metodikų. Atlikta šių tyrimų apžvalga, surinktos minėtų inžinerinių problemų sprendimo strategijos. Pateikiami konkretūs teorijos taikymo pavyzdžiai dabarties sąlygomis ir ateityje. Aptariami „dviejų asmenų nulinės sumos“ lošimų sprendiniai, taip pat neapibrėžtų aibių teorijos taikymo lošimuose atveju. Reikšminiai žodžiai: statybos vadyba, variantų atranka, lošimų teorija, „dviejų asmenų nulinės sumos“ lošimai, lošimai taikant neapibrėžtąsias aibes. First published online: 21 Oct 2010